Reconsidering the Political: A Realization of a Person or a Way to Depersonalization? - Noreikaitė, Aistė (Problemos, 2022)
This paper takes on the highly problematic question whether the political is reconcilable with the conception of a person within Robert Spaemann’s philosophy. Spaemann devotes himself to detailed explication of the moral ontology of the person, however, the political ontology in his thought is only assumed but not developed and it seems to stand in deep conflict with the developed elements of person’s ontology. The aim of the paper is to investigate whether Spaemann’s notion of the political can be reconciled with the rest of the person’s ontology and if this turn to the political rather leads to depersonalization. It is argued that it is possible to develop Spaemann’s personal ontology while integrating the concept of the political within the conception of a person.
Keywords: moral ontology; political ontology; the political; ontology of a person; Robert Spaemann